2021
DOI: 10.3389/fbioe.2021.666858
|View full text |Cite
|
Sign up to set email alerts
|

New Trends in Bioremediation Technologies Toward Environment-Friendly Society: A Mini-Review

Abstract: Graphical AbstractRedesigned enzyme for bioremediation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 145 publications
(131 reference statements)
0
21
0
Order By: Relevance
“…Including (1) increasing the temperature at the interval of 28 0 C -30 0 C, during the interaction period (10 -24) days, and decreasing to 29 0 C, during the interaction period (26 -30) days; (2) there is a change in the pH of the interaction medium at pH 6.64 which gradually decreases to pH 5.34, (the interaction medium is slightly more acidic). This condition occurs during the 8 to 30 day interaction period [24,33]; (3) it was observed that gas bubbles in the interaction medium were seen on the 8th day of contact, and the population tended to increase with increasing interaction time; and (4) the smell of fermentation from the interaction medium, observed on the 10th day of interaction until the 30th day of the measurement period. However, it is said that these four points of biodegradation parameters cannot distinguish the strength of the biodegradation activity between Bl and Sb bacteria on pyrene biodegradation [2,27,35].…”
Section: Figure 5 Bl and Sb Bacterial Cell Growth Curves On Selective...mentioning
confidence: 99%
See 1 more Smart Citation
“…Including (1) increasing the temperature at the interval of 28 0 C -30 0 C, during the interaction period (10 -24) days, and decreasing to 29 0 C, during the interaction period (26 -30) days; (2) there is a change in the pH of the interaction medium at pH 6.64 which gradually decreases to pH 5.34, (the interaction medium is slightly more acidic). This condition occurs during the 8 to 30 day interaction period [24,33]; (3) it was observed that gas bubbles in the interaction medium were seen on the 8th day of contact, and the population tended to increase with increasing interaction time; and (4) the smell of fermentation from the interaction medium, observed on the 10th day of interaction until the 30th day of the measurement period. However, it is said that these four points of biodegradation parameters cannot distinguish the strength of the biodegradation activity between Bl and Sb bacteria on pyrene biodegradation [2,27,35].…”
Section: Figure 5 Bl and Sb Bacterial Cell Growth Curves On Selective...mentioning
confidence: 99%
“…Pyrene is one of the PAHs with a relatively high level of toxicity [2,20,21]. Tests on animals showed that pyrenes cause disturbances in several vital organs, especially the kidneys, liver, digestive organs, and can enter the metabolic system, while in marine ecosystems, exposure to pyrenes interferes with the growth of various types of fish, algae, seagrass, mollusk [7,[22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…The application of consortium bacteria in the bioremediation of PAHs is considered to have higher performance and substrate degradation power and is more efficient because it is estimated that the bioremediation performance of PAHs increases to 100% (Fig. 2) [27,60,126]. The time needed by the consortium bacteria to degrade potential PAHs is less than 20 days, which can be seen from the consortium bacterial cells that still show growth [51,92].…”
Section: Contact Time (Days)mentioning
confidence: 99%
“…The results of this research have given birth to many findings, technologies, innovations and methods related to removing the toxic nature of contaminants [24,25]. Degradation, reduction, destruction, and absorption are recommended and can be applied to decompose carcinogenic pollutants in the environment [26][27][28]. This method can be called bioremediation technology if it involves the role of living organisms, including the contribution of microorganisms as biodegradators that can decompose or may be able to eliminate the toxic properties of GTP contaminants [29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, enzymes like pectinases are produced from widely available agro wastes as substrates, despite the fact that the financial implications of enzymes are an incentive for additional study into enzyme synthesis. The use of agricultural wastes for pectinase production is geared towards the creation of an environmentally or ecologically friendly way of producing valuable products [17,18]. Furthermore, exporting enzymes will help the economies of developing countries that are reliant on imports, allowing them to benefit from a share of the global enzyme market [14][15][16].…”
Section: Introductionmentioning
confidence: 99%